2008
DOI: 10.1002/smll.200800099
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Controlled Reversible Assembly and Disassembly of Gold Nanorods

Abstract: Gold nanorods exhibit rich surface-plasmon-resonance (SPR)derived properties, which have made discrete nanorods useful for many interesting applications such as optical data storage, [1] submicrometer metallic barcodes, [2] sensing, [3] biological imaging, [4] and controlled gene delivery. [5] Future scientific and technological applications of Au nanorods require the capability to assemble into complex one-, two-, or even three-dimensional (3D) functional architectures. The assembly of Au nanorods also allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
298
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(316 citation statements)
references
References 41 publications
13
298
2
Order By: Relevance
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 93%
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 93%
“…Such partial coating has been shown to favor assembly into side-by-side or end-to-end geometries, leading to superstructures with different degree of organization, complexity of collective behavior and unique optical properties. By taking advantage of interactions between small organic molecules [101] , polymers [102] , or biomolecules such as DNA [103] , oligonucleotides [104] or proteins (antibody -antigen [105] or biotin -strepavidin interactions [106] ), end-to-end and side-to-side assemblies of gold NRs have been successfully used for sensing applications [104,107] .…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
“…Charge, crystallinity, and chemical properties (such as hydrophilicity) of surfaces determine the stability, structure, and reactivity of nanoparticles. [1][2][3][4][5][6][7][8][9][10][11] In this respect, it is essential to have a capability to control and modify the surfaces of nanoparticles.…”
mentioning
confidence: 99%